TINGKAT KEBUGARAN KARDIORESPIRASI PEMAIN UKM SEPAKBOLA UNIVERSITAS MUHAMMADIYAH PURWOKERTO TAHUN 2017 - Yudha Febrianta; Sriyanto Sriyanto (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2019)
This study aims to measure the cardiorespiratory fitness of players in the Football Student Activity Association of the Muhammadiyah University of Purwokerto in 2017. This study is a qualitative descriptive method. The population is all players of Football Student Activity Association of the Muhammadiyah University of Purwokerto, with a total of 16 people (respondents). The instrument of the study is the Multi-Stage Test with the reliability of 0.9 and the validity of 0.6. Data analysis techniques used are descriptive with percentages and 6 categories; excellent, very good, good, moderate, lack, and fail. The results show that the level of cardiorespiratory fitness of the football players in the Student Activity Association of the Muhammadiyah University of Purwokerto is in the medium category, no one in the fail and lack category, 8 people (50.00%) with the moderate category, 4 people (25.00%) with the good category, 2 people (12.50%) with the very good, and 2 people (12.50%) with the excellent category.